A principal component analysis is conducted for a case series quality appraisal checklist - Guo, Bing; Moga, Carmen; Harstall, Christa; Schopflocher, Don (Journal of clinical epidemiology, 2016)
Because of a lack of a control group, a case-series study is considered one of the weaker study designs from which to obtain evidence on treatment effectiveness. Under certain circumstances, however, this is the only available evidence to inform health-care decisions. This study's intent was to develop and validate a quality appraisal checklist specifically for case-series studies. A modified Delphi process was used to develop the checklist, which was then used by multiple researchers to appraise a random sample of 105 case-series studies. A principal component analysis of these appraisals was conducted to further refine the checklist. The modified Delphi process resulted in a 20-criterion checklist. The principal component analysis of the appraisals for the 105 case-series studies revealed two components. The first component (10 criteria) indicated the extent to which a case series presented traditional features of a statistical hypothesis-testing paradigm. The second component (seven criteria) indicated whether detailed descriptions of the subjects' characteristics that might feature in the experimental design were present, particularly in judgments about the likelihood of confounding. This quality appraisal checklist may be useful in assessing case-series studies, but further validation of the checklist is required.